The Effect of Variations in Absorbents from Coconut Shell (Cocos Nucifera), Candlenut Shell (Aleurites Moluccanus), and Bidara Wood (Ziziphus Mauritiana) on the Characteristics of Mercury-Contaminated Wastewater - Arif Munawir; Shafwan Amrullah (Universitas Muhammadiyah Mataram, 2025)
Illegal Gold Mining in several areas of West Nusa Tenggara, particularly in Sumbawa, has had negative impacts on the environment, such as natural damage and environmental pollution, including water contamination with mercury. This study aims to determine the effect of variations in absorbents from coconut shell, candlenut shell, and bidara wood on the physical and chemical characteristics of mining wastewater. The method used in this research is experimental, involving testing with filtration equipment. This study employs three treatments (absorbent variations) and three repetitions for each treatment. The results indicate that the use of activated carbon from coconut shell, candlenut shell, and bidara wood can affect the color, TDS, pH, and mercury content in mining wastewater. Among the three variations of activated carbon, the treatment with bidara wood activated carbon proved to be the most effective in clarifying water color with a score of 1.4 (very clear), reducing TDS by 3570 ppm, improving pH to 7.63, and decreasing mercury content in the water to 1.39 µg/L.